Communication-Based Conflict Management in a Multicultural Work Environment: Implications for the Effectiveness of Human Resources Management - Verry Albert Jekson Mardame Silalahi (Yayasan Inspirasi Merah Putih Indonesia, 2025)
Globalization and cross-border labor mobility have pushed modern organizations to become increasingly multicultural, thereby increasing the complexity of work interactions and potential conflicts based on differences in values, language, and communication norms. This study aims to analyze the forms of conflict in a multicultural work environment, identify the communication strategies used in its management, and explain its implications for the effectiveness of human resource (HR) management. The research uses a qualitative descriptive approach with data collection techniques through in-depth interviews, observations, and documentation. Informants consist of HR managers, supervisors, and cross-cultural employees in multicultural organizations. Data analysis is carried out through data reduction, data presentation, and thematic conclusion drawn. The results of the study show that the dominant conflicts include differences in work values, communication styles, and perceptions of authority. Effective communication strategies in conflict management include open dialogue, mediation, cross-cultural communication, and interpersonal communication training. The implementation of this strategy has positive implications for improving team performance, reducing turnover, increasing job satisfaction, and strengthening an inclusive organizational culture. This study emphasizes that communication strategy plays a role as a mediating variable that connects the dynamics of multicultural conflict with the effectiveness of human resource management, thus making a theoretical and practical contribution to the development of communication-based conflict management models in multicultural organizations.